The Analysis of the Impact of Organizational Silence on the Organizational Citizenship Behavior among Employees in the Algerian Public Administration - Ghediri, Daoud; Boussalem, Aboubaker (Finance and Business Economies Review, 2023)
The current study aims to measure the impact of organizational silence on organizational citizenship behavior among employees in the public administration in Algeria. In order to achieve the goal of the study, (191) opinions were surveyed, and chosen in a way the random sample, where the data were subjected to statistical analysis using Jeffrey's Amazing Statistics Program (JASP). The results of the questionnaire analysis showed that the manifestations of organizational silence among employees in the Algerian public administrations was high, according to the employees’ perceptions, and it was also found that the respondents had an medium level in the practice of organizational citizenship behaviors. Importantly, the results show that there is an inverse effect, which was with a medium degree (-0.278) and statistically significant for defensive silence and a weak effect (-0.109 and -0.012) and not statistically significant for acquiescent silence and prosocial silence, respectively, on organizational citizenship behavior